Beyond verification: Flesh witnessing and the significance of embodiment in conflict news. (March 2022) - Chouliaraki, Lilie; Al-Ghazzi, Omar
Platform journalism in the global North is caught within a fragile political economy of emotion and attention, defined, on the one hand, by the proliferation of user-generated, affective news and, on the other, by the risk of fake news and a technocratic commitment to verification. While the field of Journalism Studies has already engaged in rich debates on how to rethink the truth conditions of user-generated content (UGC) in platform journalism, we argue that it has missed out on the ethico-political function of UGC as testimonials of lives-at-risk. If we wish to recognize and act on UGC as techno-social practices of witnessing human pain and death, we propose, then we need to push further the conceptual and analytical boundaries of the field. In this paper, we do this by introducing a view of UGC as flesh witnessing, that is as embodied and mobile testimonies of vulnerable others that, enabled by smartphones, enter global news environments as appeals to attention and action. Drawing on examples from the Syrian conflict, we provide an analysis of the narrative strategies through which flesh witnessing acquires truth-telling authority and we reflect on what is gained and lost in the process. Western story-telling, we conclude, strategically co-opts the affective dimension of flesh witnessing – its focus on child innocence, heroic martyrdom or the data aesthetics of destruction – and selectively minimizes its urgency by downplaying or effacing the bodies of non-western witnesses. This preoccupation with verification should not be subject to geopolitical formulations and needs to be combined with an explicit acknowledgement of the embodied voices of conflict as testimonies of the flesh whose often mortal vulnerability is, in fact, the very condition of possibility upon which western broadcasting rests.